Rising threats of hospital-borne multidrug resistant Stenotrophomonas maltophilia in the adolescent at Najran, Saudi Arabia - Aedh, Abdullah (The Journal of Infection in Developing Countries, 2023)
Introduction: The aim of this study was to investigate the clinical isolates of patients infected by Stenotrophomonas maltophilia (S. maltophilia) in the intensive care unit (ICU) at King Khalid Hospital, Kingdom of Saudi Arabia (KSA), and to identify the healthcare complications, antimicrobial resistance patterns, and risk factors associated with infection for this emerging pathogen. Methodology: In this cross-sectional observational study, patients admitted in the ICU (n = 127) were analyzed, and 36 non-duplicating S. maltophilia strains were clinically isolated in King Khalid Hospital, KSA between September 2020 and April 2021. Antimicrobial susceptibility testing was performed using standard antibiotics (n = 13). Results: In this study, 36 clinical isolates of S. maltophilia were identified as true infection pathogens. The main locations of S. maltophilia infection were in the respiratory tract (13, 36.1%) followed by surgical area (10, 27.7%) and wound infection (7, 19.4%). The significant risk factors included a medical history of respiratory infection, exposure to a bomb blast, and infected from an implant (p < 0.05). Among the 36 clinical isolates, 5 strains were positive for extended spectrum beta-lactamase (ESBL). The most active antimicrobials were vancomycin (69.4% sensitivity) and trimethoprim/sulfamethoxazole (80.5% sensitivity). Conclusions: Our study concludes that S. maltophilia is an emerging nosocomial pathogen in the ICU, indicating the possibility of direct or indirect transfer from one person to another. Specific identification and active antibiotic susceptibility testing of S. maltophilia are needed for the treatment management and prevention of spread of the S. maltophilia pathogen.